2009
DOI: 10.1590/s0037-86822009000200019
|View full text |Cite
|
Sign up to set email alerts
|

Infecções oportunistas por leveduras e perfil enzimático dos agentes etiológicos

Abstract: Infecções por leveduras são freqüentes em imunocomprometidos, contudo espécies emergentes têm alterado o perfil epidemiológico. A habilidade de secretar proteases tem sido associada à patogenicidade do gênero Candida. Esta pesquisa teve como objetivos diagnosticar leveduroses em pacientes imunocomprometidos e avaliar a virulência dos agentes etiológicos baseado em teste de secreção de protease utilizando soro de albumina bovina como substrato. Do total de 104 pacientes estudados, 19 apresentaram episódios de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
2
3
0
4
Order By: Relevance
“…Similarly, the present study showed a high prevalence of Candida non-albicans species in the group of children with AIDS -a condition equally favorable to the emergence of opportunistic infections -and in the groups of children without AIDS. The most frequent Candida non-albicans species were C. parapsilosis, C. famata, and C. tropicalis, as reported by Macedo et al 17 . The main clinically relevant Candida species are Candida albicans, C. parapsilosis, and C. tropicalis.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Similarly, the present study showed a high prevalence of Candida non-albicans species in the group of children with AIDS -a condition equally favorable to the emergence of opportunistic infections -and in the groups of children without AIDS. The most frequent Candida non-albicans species were C. parapsilosis, C. famata, and C. tropicalis, as reported by Macedo et al 17 . The main clinically relevant Candida species are Candida albicans, C. parapsilosis, and C. tropicalis.…”
supporting
confidence: 70%
“…The main clinically relevant Candida species are Candida albicans, C. parapsilosis, and C. tropicalis. However, an increasing number of cases of superficial and invasive diseases caused by emerging Candida species (species that have appeared recently in a population or whose incidence and geographic range has increased rapidly) have been described and include C. dubliniensis, C. kefyr, C. famata, C. utilis, and C. norvegensis, among others [17][18] . In the present study, the Candida species considered the most important clinically and that are emerging were isolated from the oral cavity of children exposed and non-exposed to HIV and of children with AIDS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum temperature of growth for each isolate was determined according Barnett et al (2000) and De Hoog et al (2000). The isolates which presented ambiguous identification were further analysed by VITEK-2 XL (bioMerieux, Brazil) according to previous reports (Macedo et al , 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Entretanto, é capaz de causar infecção se o equilíbrio com o hospedeiro é quebrado como nos casos em que se observa baixa imunidade nos pacientes; sob manifestações clínicas e fatores de risco relacionados à neutropenia, diabetes mellitus, tuberculose pulmonar, lúpus eritematoso sistêmico, síndrome da imunodeficiência adquirida (SIDA ou AIDS), uso de drogas imunossupressoras, mucosite induzida por quimioterapia, altas doses de irradiação e antibioticoterapia (MACEDO et al, 2009;MARR, 2005). Pacientes transplantados apresentam alto risco de desenvolver infecções sanguíneas fúngicas.…”
Section: Introductionunclassified